Regional Strain Score as Prognostic Marker of Cardiovascular Events From the Multi-Ethnic Study of Atherosclerosis (MESA) - Pezel, Theo; Bluemke, David A.; Wu, Colin O.; Lima, João A. C.; Ambale Venkatesh, Bharath (Frontiers in Cardiovascular Medicine, 2022)
Background Left ventricular (LV) circumferential strain (Ecc) is an accurate indicator of regional myocardial function, particularly using the regional Ecc or layer-specific strain. Aim This study aimed to investigate the prognostic value of a regional strain score (RSS) for predicting the incident of heart failure (HF) and coronary heart disease (CHD) in a population without a history of cardiovascular disease at baseline. Materials and Methods Data from participants in the Multi-Ethnic Study of Atherosclerosis (MESA) who underwent tagged magnetic resonance imaging for strain determination were analyzed. Using −17% and −10% as Ecc cut-offs, each segment was rated from 0 to 2 points according to the Ecc value of each layer. The endo-Ecc, mid-Ecc, and epi-Ecc values from the 16-segment model were used to calculate three RSS: Endo-, Mid-, and Epi-RSS, respectively, which were defined as a percentage of good LV regional function. The Intramyocardial-RSS was the sum of these three RSS. Cox proportional hazard models were used to evaluate the association between each RSS and incident HF and hard CHD. Results Among the 1,506 participants (63.3 ± 9.4 years, 54.6% men), 122 cases of hard CHD and 91 cases of HF were observed [median (IQR) follow-up 15.9 (12.9–16.6) years]. After adjustment, Mid-, Epi-, and Intramyocardial-RSS values <50% were independently associated with HF [adjusted HR 1.43; 95% CI (1.08–2.87), p = 0.004; HR 1.80; 95% CI (1.12–3.07), p < 0.001; and HR 2.01; 95% CI (1.19–3.20), p < 0.001]. After adjustment, Endo-, Mid-, Epi-, and Intramyocardial-RSS <50% were also independently associated with hard CHD [adjusted HR 1.31; 95% CI (1.03–1.51), p = 0.04; HR 1.79; 95% CI (1.26–2.57), p < 0.001; HR 2.03; 95% CI (1.45–3.40), p < 0.001; and HR 2.28; 95% CI (1.51–3.53), p < 0.001]. Conclusions Layer-specific regional Ecc, assessed by RSS, provides a robust, independent predictive value for incident HF and hard CHD in asymptomatic participants without any history of previous clinical cardiovascular disease. Clinical Trial Registration Unique identifier: NCT00005487.